On Capitalisation of the Concept of Work in Economic Theory - Nowak, Krzysztof (Studia Historiae Oeconomicae, 2012)
The following paper discusses capitalisation of the concept of work within economics. While representatives of the classical political economy considered labour both as a technical factor of production and as a social relation of production, the neoclassical economic theorists seem to systematically neglect the latter aspect on behalf of the former. The concept of work initially included elements such as: ownership of labour-force, effort, duration in time-units, professional skills, social competences and creative component, all stemming from innate abilities, practical experience and formal education. Capitalisation, on the other hand, implied taking the above mentioned components one by one and building consecutive human, social, and creative capital theories. Although, this operation can be undertaken in order to quantify various previously immeasurable or difficult-to-measure components of the standard concept of labour-power, one has to pay attention to the possible misuses and abuses of capitalisation.